Ancient Egypt and early China : state, society, and culture - Barbieri-Low, Anthony J. (Anthony Jerome), 1967- (Seattle : University of Washington Press, 2021)
"Although they existed more than a millennium apart, the great civilizations of New Kingdom Egypt (ca. 1548-1086 BCE) and Han dynasty China (206 BCE-220 CE) shared intriguing similarities. Both were centered around major, flood-prone rivers--the Nile and the Yellow River-and established complex hydraulic systems to manage their power. Both spread their territories across vast empires that were controlled through warfare and diplomacy and underwent periods of radical reform led by charismatic rulers--the "heretic king" Akhenaten and the vilified reformer Wang Mang. Universal justice was dispensed through courts, and each empire was administered by bureaucracies staffed by highly trained scribes who held special status. Egypt and China each developed elaborate conceptions of an afterlife world and created games of fate that facilitated access to these realms. This groundbreaking volume offers an innovative comparison of these two civilizations. Through a combination of textual, art historical, and archaeological analyses, Ancient Egypt and Early China reveals shared structural traits of each civilization as well as distinctive features"--
Introduction -- The landscapes of the Nile and Yellow River -- Empire and diplomacy -- Akhenaten, Wang Mang, and the limits of reform -- Legal principles and the administration of justice -- Scribal culture in life and death -- Providing a model afterlife / Anthony J. Barbieri Low, Marissa A. Stevens -- Gaming the way to paradise -- Epilogue.
Includes bibliographical references and index.
online resource; title from digital title page (viewed on June 22, 2021).
JSTOR
Keywords: Civilization, Ancient; Comparative civilization; Egypt -- Civilization -- To 332 B.C.; Egypt -- History -- New Kingdom, ca. 1550-ca. 1070 B.C.; China -- Civilization -- 221 B.C.-960 A.D.; China -- History -- Han dynasty, 202 B.C.-220 A.D.; Civilisation ancienne; Civilisation comparée.; Égypte -- Civilisation -- Jusqu'à 332 av. J.-C.; Égypte -- Histoire -- ca 1550-1070 av. J.-C. (Nouvel Empire); Chine -- Civilisation -- 221 av. J.-C.-960.; Chine -- Histoire -- 202 av. J.-C.-220 (Dynastie des Han); HISTORY / Asia / China; Civilization; Civilization, Ancient; Comparative civilization; Han Dynasty (China); China; Egypt; To 960; Electronic books; History